GENDER INTELLIGENCE AS STRATEGIC CAPABILITY: A TRANSFORMATIONAL FRAMEWORK FOR INCLUSIVE ORGANIZATIONAL LEADERSHIP - Rosita Indrawati (FISIP Universitas Malikussaleh, 2026)
Gender inequality in organizations persists despite widespread formal equality policies, primarily because such policies address procedural compliance rather than the structural and cultural mechanisms that sustain bias. This study aims to develop a six-dimension transformational framework of gender intelligence that reconceptualizes gender equality as a strategic organizational capability. Employing a qualitative case study design, in-depth interviews and non-participant observation were conducted within a private sector organization that has been in operation for nearly nineteen years. Four participant categories were selected through purposive sampling, representing human capital management, employees of varying tenure, and managerial staff. Data were analysed through iterative open, axial, and selective coding. Findings reveal that the organization exhibits symbolic compliance with formal gender equality commitments while patriarchal assumptions operate at the level of basic organizational culture, constraining women's access to strategic leadership. The proposed framework encompasses: transitioning from compliance to gender intelligence, developing a disruptive leadership pipeline, enacting deep culture change, reframing feminine leadership as strategic advantage, closing the policy–practice gap, and implementing integrated multi-level interventions. The study concludes that sustainable gender transformation requires simultaneous structural, cultural, cognitive, and systemic change rather than fragmented initiatives.